Turbulent forced convection heat transfer of nanofluids with twisted tape insert in a plain tube - Azmi, W.H. (Elsevier Ltd, 2014)
Experimental determination of heat transfer coefficients of SiO 2/water and TiO2/water nanofluid up to 3 volume concentration flowing in a circular tube is undertaken. The investigations are conducted in the Reynolds number range of 5000 to 25000 at a bulk temperature of 30Â°C. The experiments are undertaken for flow in a circular tube with twisted tapes of different twist ratios in the range of 5 â¤H/Dâ¤ 93. The heat transfer enhancement is inversely increased with twist ratio. The heat transfer coefficient of SiO2/water nano fluid at 3.0 volume concentration is 27.9 higher than water flow for the same twist ratio of five. However, the value of heat transfer coefficient of TiO2/water nanofluid evaluated at the same concentration is 11.4 greater than water for twist ratio five. Regression equations for Nusselt number estimation are developed valid for water and nanofluid flow with twisted tape inserts under turbulent flow conditions. Â© 2014 Published by Elsevier Ltd.